Constitutional study on executive-legislative relations in Chinese polities Hong Kong and Taiwan - Guo, Y (2015)
This thesis will compare Hong Kong and Taiwan's constitutional development to enrich our understanding of the constitutional design of Executive-Legislative relations (E-L relations) during democratization. In each jurisdiction, the ad hoc constitutional transplants from the different traditions － the Western tradition of the separation of powers, the Chinese tradition of paternal state， and the communist tradition of Leninist party-state--caused institutional discord after democratization. Authoritarianism might have succeeded in masking this problem but during democratic transformation, when the nominal constitution starts to function, these institutional discords crippled effective governance. In particular, the failure of the chief executive in Hong Kong and Taiwan offers a contrast to Linz's famous observation of the "perils of presidentialism." It also presents a puzzle that deserves academic attention. The analytical tools utilized to construct this paper include the agenda-setting and veto player theories from the study on political institutions. The constitutional configuration and mechanisms of agenda-setting and veto-playing will be used to explain the institutional origin of the governance failure in these regions. This paper will first identify the general agenda-setting and veto-playing patterns in the archetypical Western democracies; second, it will apply this framework to Hong Kong and Taiwan to test how these institutions are manipulated during constitutional borrowing, and how governance failure is precipitated. The first chapter discusses the theoretical framework. The major themes of this chapter will be frequently revisited during later chapters. It will first give a general account of the executive and legislative branches. The tasks, powers, structure and personnel of both will be discussed to lay a foundation for later inter-branch analysis. Subsequently, it will summarize the different theories and ideas about power separation and balance in Western democracy, Chinese tradition and the communist regime, respectively. Next, the agenda-setting and veto-playing approach on E-L relations will be discussed. The relevant constitutional and legal mechanisms will be identified and analyzed. It will end with a brief summary.